Development of Vaccine Prototype Against Zika Virus Disease of Peptide-Loaded PLGA Nanoparticles and Evaluation of Cytotoxicity - (:unkn) unknown (SPRINGER, 2019)
Zika virus has recently evolved from an obscure mosquito-borne pathogen to an international public health concern. People with Zika virus disease can have indications including mild fever, skin rash, conjunctivitis, muscle pain, malaise or headache. Effective vaccines are needed for controlling and preventing the disease. In the current study, we aim to design the substructure for vaccine against Zika virus by forming antigenic peptide epitope of the disease. Zika peptide loaded poly (lactic-co-glycolic acid) (PLGA) nanoparticles have been fabricated in the present work as a potential artificial vaccine. UV and FT-IR Spectrophotometers and ZetaSizer were used for studying the nanoparticles, and Scanning Electron Microscope was used for morphological examination. The nanoparticles (NPs) yield, encapsulation efficiency, the peptide loading capacity were determined and in vitro release of the peptide was studied. Cytotoxic effects of the various concentrations of Zika peptide, blank PLGA nanoparticles and Zika peptide loaded PLGA nanoparticles on ECV304 human epithelial cells were determined via MTT assay. The present paper could be considered as one of the important steps in the use of nanoparticles for constructing the new generation of vaccination systems.
Keywords: Nanoparticles; Peptide; PLGA; Vaccine; Zika virus; Cytotoxicity